新加坡初级学院学生 “把” 字句的使用情况 = The use of BA sentences by Singapore Junior College students - 洪菱霜 Ang, Alicia Ling Shuang (Nanyang Technological University, 2021)
在现代汉语中，“把”字句是一种较为特殊又复杂的句式。其基本句法格式为：主语+把+宾语+动词性谓语。而谓语动词后的部分可再细化，分成不同的句式结构。该句式的语用特征不仅是突出句中的宾语，也突出动词和其前后的成分。因此，“把”字句的使用限制较多，因而较难掌握，造成偏误屡次出现。而针对“把”字句偏误现象的研究，许多前人都着重于韩国、印尼、英语国家等的汉语学习者，几乎没有以新加坡学生为对象的研究。为了考察新加坡学生对“把”字句的掌握程度，本研究以新加坡初级学院学生的作文为语料，分析“把”字句的偏误类型及学生对“把”字句不同句式类型的使用情况，并将其研究结果和新加坡语言环境的概况结合，探析偏误发生的可能原因。本研究有三个主要发现：一、新加坡学生最常出现“错用”偏误类型，其中句子成分遗漏的现象最严重。二、新加坡学生最常用的句式是“S+把+O+V+到/在/给/向+O2”；最常出错的句式是“S+把+O+V+作/成/为+O2”。三、偏误发生的可能原因为英语和目的语知识的负迁移。希望本文能为“把”字句偏误研究和新加坡教育工作者在“把”字句的教学上贡献新知识及提供参考，从而加强学生对“把”字句的掌握程度，以提高他们的汉语水平。BA sentence is a unique, yet complex sentence structure in Mandarin Chinese. Its basic syntactic structure is “Subject + BA + Object + Verbal predicate” but can be further divided into different types based on the structures of the verbal predicate. The major semantic-pragmatic feature of the BA sentence is to highlight the object, the verb, and its components before and after it. Hence, the BA sentence tends to be more restrictive on its sentence elements. As a result, it can be rather difficult to master, resulting in repeated errors occurring. Current studies regarding the misuses of BA sentences mainly target Mandarin learners from South Korea, Indonesia and English-speaking countries etc., while there is hardly any research done on students in Singapore. The aim of this study is to analyse the usage of BA sentences among Singapore junior college students based on their essays. The research analyses the types of errors occurred, the usage of the different sentence types, and discusses the possible causes of the errors, while taking Singapore’s context into account. There are three major findings of this study: 1. “Wrong usage” is the most frequent error among Singapore students, in which the omission of sentence elements is the most common error. 2. “S+把+O+V+到/在/给/向+O2” is the most-used sentence type among Singapore students; “S+把+O+V+作/成/为+O2” is the most error-prone sentence type. 3. Repeated errors may have occurred due to negative transfer of English and negative transfer of knowledge of the target language. This thesis hopes to contribute new knowledge and provide reference for the research on the errors and teachings of BA sentences in Singapore, so as to strengthen the students’ command of it and ultimately, improve their Mandarin proficiency.